Freezing-thawing response of sand-kaolin mixtures in oedometric conditions - Viglianti Andrea; Guida Giulia; Casini Francesca (E3S Web of Conferences, 2024)
The freezing and thawing cycles applied to soils can often be causes of irreversible instabilities, uplift, or subsidence. These phenomena can be both natural (e.g. permafrost regions) or artificially induced (e.g. artificial ground freezing (AGF), as an excavation earth support technique for tunnelling). When the soil temperature falls below 0°C, the liquid water changes phase turning into ice. The freezing process generally implies an expansion of the soil element due to (i) the lower density of the migration of the ice and (ii) the pore water toward the frozen front. The complex interaction between the solid grains, the water and the ice formation during freezing determines the soil’s overall thermo-hydromechanical (THM) behaviour. Sandy mixtures with different percentages of kaolin were tested on an oedometer developed at the Geotechnical Laboratory of Universita degli Studi di Roma Tor Vergata, working at temperatures below zero. The samples were compressed under five different vertical stresses (50, 100, 200, 400 and 800 kPa, respectively), and then a freezing and thawing cycle was applied by steps to a minimum temperature of -20°C. The experimental results regarding temperature evolution, vertical displacements, and liquid water amount monitored are discussed and interpreted through a micro-to-macro approach. The data analysis revealed interesting outcomes that characterise mechanical and hydraulic hysteresis during freezing and thawing processes. A deeper understanding of the coupled phenomena that occur during the freezing and thawing cycles is supposed to contribute to developing a constitutive model that can reproduce the irreversible volumetric response of frozen soils.